Effectiveness of e-book writing software on TESL pre-service teachers’ ESL academic writing performance - Kee, Li Li (2020)
In the preparation to serve as English as a Second Language (ESL) writing teachers, the Teaching English as a Second Language (TESL) pre-service teachers need to acquire writing proficiency as well as writing pedagogies. They need to be aware of their own writing performance, their understanding of the writing process and more importantly their ability to teach ESL writing. Additionally, the amalgamation of digital technologies and process-based writing approach (PBWA) seems viable for writing instruction in the 21st century education. There are few studies, which focus on the use of e-book writing software in ESL academic writing that closely incorporates PBWA in a recursive manner. Therefore, this study investigates the effectiveness of e-book writing software and the ways it affects the TESL pre-service teachers’ ESL academic writing performance (i.e., content, communicative achievement, organisation and language). The social constructivism theory, the concept of digital literacies, the bridging activities model and PBWA synergised to function in tandem and corresponding ways. Within the digital environment as the social context, the research participants partook in the writing process stages generally implemented in a sequence and done in a recursive manner applying the technological knowledge to research, read and write the academic papers as an e-book by using different modality, modes and media. The quasi-experiment was conducted on two groups of TESL pre-service teachers (N = 40) from one Institute of Teacher Education Malaysia (ITEM), which were selected through purposive sampling. The main quantitative data of pre- and post-tests, observations and students’ essays were analysed using SPSS Version 23. Additionally, the qualitative supplementary data of reflective journal entries, focus group interview responses and students’ essays were analysed using qualitative content analysis, deductive approach and document analysis. The paired and independent samples t-tests and Hotelling’s T2 (i.e., a special case of one-way MANOVA) yielded statistically significant differences in the mean scores. These results reveal that the utilisation of e-book writing software improves the participants’ ESL academic writing performance and the four writing constructs. It enables the participants to manage their writing practices in the writing process, increases the participants’ motivation in academic writing, provides convenience in the writing process and helps with the recursiveness of the writing process. It also enables the participants to develop and shape the content, promote the audience-based writing, improve the text organisation and promote the correct use of vocabulary and grammar. The utilisation of e-book writing software is advantageous for the pre-service teachers as it proposes an effective way in enhancing the writing process stages and promotes writing academic papers with increased motivation. To sum up, the utilisation of e-book writing software is able to ignite the positive change in the TESL pre-service teachers’ ESL academic writing that will thus give impetus in their provision of ESL writing instruction in the future.